2008
DOI: 10.1080/08860220802422044
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of DNA Oxidation and Antioxidant Activity in Hypertensive Patients with Chronic Kidney Disease

Abstract: The aim of this study was to evaluate the oxidative DNA damage, antioxidant activity, and effects of antihypertensive drugs on oxidative stress in hypertensive patients with different stages of chronic kidney disease (CKD). Fifty-three non-dialyzed hypertensive CKD patients were included by the study. Serum and urinary 8-hydroxydeoxy guanosine (8-OHdG) levels (as a marker of oxidative DNA damage), serum superoxide dismutase (SOD), and glutathione peroxidase (G-Px) activities (as antioxidant enzymes) were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 29 publications
2
15
2
Order By: Relevance
“…At the same time, the sexual desire values were increased following 48 weeks of treatment in the F+I group. This result is consistent with previous research [29,30]. However, the scores for the other domains and the total IIEF scores showed no improvement compared with baseline.…”
Section: Discussionsupporting
confidence: 83%
“…At the same time, the sexual desire values were increased following 48 weeks of treatment in the F+I group. This result is consistent with previous research [29,30]. However, the scores for the other domains and the total IIEF scores showed no improvement compared with baseline.…”
Section: Discussionsupporting
confidence: 83%
“…Enhanced H 2 O 2 excretion [27,37] and lower GPx activity [31,36] has been reported in adult SHR when compared with normotensive WKY rats. Reduced GPx activity [7,30] and enhanced H 2 O 2 levels [13] have also been reported in patients with hypertension. Interestingly, normotensive volunteers with a family history of hypertension have been found to have higher plasma H 2 O 2 levels than those in normotensives without a family history of hypertension [14].…”
Section: Discussionmentioning
confidence: 93%
“…Literature concerning antioxidant enzyme activities in red blood cells in arterial hypertension is confusing, showing a decrease, an increase, or unaltered activities in SHR compared with WKY rats [48,49]. In serum of hypertensive patients with different stages of chronic kidney disease, Dincer et al found a decrease in the activity of GSH-Px and an increase in that of SOD [10]. Also, the activities of GSH-Px and SOD in whole blood and in mononuclear peripheral cells were lower in hypertensive patients [35].…”
Section: Discussionmentioning
confidence: 98%